Simultaneous metabolomics analysis of atrial tissue, pericardial fluid and blood reveal novel metabolite signatures of the pathophysiology and biomarkers related to permanent atrial fibrillation. (3rd October 2022) - Harju, K; Tuomainen, T; Lehtonen, M; Karkkainen, O; Linna-Kuosmanen, S; Halonen, J; Hartikainen, J; Tavi, P
Abstract: Introduction: Atrial fibrillation (AF) is the most common, complex, and clinically relevant arrhythmia [1]. It is a growing medical condition associated with significant morbidity and mortality, but its pathophysiology has remained widely unknown [2]. Aims: We aim to unravel the complex pathophysiological mechanisms of AF and identify clinically relevant AF-related metabolites. We aim to identify targets for therapeutical interventions and biomarkers for AF diagnostics. Our study material is unique as we can safely study human heart and pericardial fluid in addition to blood, that has been mainly examined in previous studies. Material and methods: Patients recruited were undergoing cardiac surgery due to valve defects at the University Hospital. For our research, we collected preoperative blood samples and intraoperative right atrial appendage biopsy and pericardial fluid. For our metabolomics study on AF patients, we selected 16 patients with permanent AF and 17 age, gender and underlying disease matched control patients (Fig. 1). Liquid chromatography mass spectrometry (LC-MS) was used to identify molecules and metabolites related to AF. We integrated targeted assays for absolute quantification of specific metabolites with untargeted metabolomics to discover novel compounds and metabolites. Results: Untargeted mass spectrometry (MS) metabolite analysis identified altogether 15751 molecular features and metabolites divided unequally between the sample types (Fig. 2). Altogether, we found 1041 (p<0.05) metabolites from the heart tissue, 774 from the pericardial fluid and 382 from the blood. There were 61 metabolites associated with permanent AF that were found in all three sample types. The approach and our research set-up also allowed us to distinguish metabolites that entered directly from heart tissue to blood and those that remained in heart tissue and pericardial fluid. According to the identified metabolites in the heart tissue, permanent AF was associated with a clear metabolite signature including signs of dysregulated energy -, histidine -, glutathione -, purine -, sugar -, and lipid metabolism and antioxidant defense. Altogether we identified altered, circulating AF-related biomarkers including novel carnitines and acylcarnitines, aminoacids, metabolites from immune response and lipid metabolism. Among the highest statistical significance with qualifiable difference (multivariate α-level 0.0007) we found two novel circulating molecules with known MS spectrum and molecular weight. Conclusions: We identified totally new pathophysiological processes and novel potential metabolites related to permanent AF to be used as AF biomarkers. Permanent AF is associated with dysreculation of multiple biologically relevant metabolic pathways. Funding Acknowledgement: Type of funding sources: Foundation. Main funding source(s): Academy of FinlandThe Finnish Foundation for Cardiovascular Research